Multi-component subunit vaccines against Theileria parva - McKeever, Declan J. (International Livestock Research Institute, 1999)
Cattle that recover from Theileria parva infection are solidly immune to rechallenge with homologous parasites. Most of the ILRAD/ILRI immunological research into the disease has focused on defining the basis of this protection. Over 15 years of basic and applied immunological research at ILRAD/ILRI have demonstrated that protection in T. parva immune cattle is primarily mediated by parasite-specific Cytotoxic T. lymphocytes (CTL). This paper summarises the status of the research and options including antigens, in vivo activation requirements and antigen delivery systems.